2001
DOI: 10.1017/s0266467401001596
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a strong drought on Amazonian forest fragments and edges

Abstract: ABSTRACT. Little is known about how climatic variability affects fragmented forests and their abrupt edges. We contrasted effects of the 1997 El Niño drought between fragmented and continuous forests in central Amazonia, using long-term data on tree mortality. For 23 permanent 1-ha plots, annualized mortality rates of trees Ȅ 10 cm diameter at breast height (dbh) were compared among a 'baseline' interval of 5-17 y before the drought, a 12-16-month interval during the drought, and a 12-13-month interval after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 65 publications
1
74
1
1
Order By: Relevance
“…In particular, it is not possible to distinguish with certainty whether increases are driven by widespread recovery from a previous disturbance, or by an overall increase in forest productivity. In Amazonia, mega El Niñ o events (Meggers 1994) provide one mechanism that potentially could drive a broad-scale increase in AGB owing to succession, as it is well known that El Niñ o events cause increased tree mortality (Condit et al 1995;Nakagawa et al 2000;Laurance et al 2001). However, the increase in AGB reported here has occurred despite two of the most severe El Niñ os on record occurring during the monitoring period (Malhi & Wright 2004), suggesting that El Niñ o events may not necessarily dominate tropical forest dynamics over decadal time-scales (Williamson et al 2000).…”
mentioning
confidence: 99%
“…In particular, it is not possible to distinguish with certainty whether increases are driven by widespread recovery from a previous disturbance, or by an overall increase in forest productivity. In Amazonia, mega El Niñ o events (Meggers 1994) provide one mechanism that potentially could drive a broad-scale increase in AGB owing to succession, as it is well known that El Niñ o events cause increased tree mortality (Condit et al 1995;Nakagawa et al 2000;Laurance et al 2001). However, the increase in AGB reported here has occurred despite two of the most severe El Niñ os on record occurring during the monitoring period (Malhi & Wright 2004), suggesting that El Niñ o events may not necessarily dominate tropical forest dynamics over decadal time-scales (Williamson et al 2000).…”
mentioning
confidence: 99%
“…The encroachment of LSMA is converting the continuous natural vegetation cover of Butana into spatially isolated patches. Such fragmentation has reduced the capacity of the rangeland to sustain the livelihood of local populations by transforming the rangeland into isolated homogeneous habitat patches that stop floral and faunal migration and reduce the ability of natural regeneration of native vegetation (Henderson et al 1985;Laurance et al 2001). Stokes et al (2006) identified changing patterns of land use as the main cause of rangeland fragmentation in many developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that might promote edge-effect variability include the age of habitat edges (Matlack 1993), edge aspect (Turton and Freiburger 1997), fragment size (Ewers et al 2007), the structure of the adjoining matrix vegetation (Pohlman et al 2007), seasonality (Young and Mitchell 1994), extreme weather events (Laurance et al 2001), and fires (Cochrane and Laurance 2002).…”
Section: Introductionmentioning
confidence: 99%